Kam komplektli sinflarda mustaqil ishlarni tashkil etishning o‗ziga xos jihatlari - Yuldosheva, S.A (SCIENCE and SOCIETY, 2024)
This article describes the factors of the organization of complete classes in low-equipped general education institutions, the advantages and problems of the educational process, the specific aspects of using independent work, individual assignments and handouts in the organization of effective education.
Keywords: low-equipped general education institutions; complete classes; organization of the educational process; independent work; individual assignments and handouts